1998
DOI: 10.1152/jappl.1998.85.5.1929
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to periodic breathing with assisted ventilation during sleep in normal subjects

Abstract: Assisted ventilation with pressure support (PSV) or proportional assist (PAV) ventilation has the potential to produce periodic breathing (PB) during sleep. We hypothesized that PB will develop when PSV level exceeds the product of spontaneous tidal volume (VT) and elastance (VTsp . E) but that the actual level at which PB will develop [PSV(PB)] will be influenced by the DeltaPCO2 (difference between eupneic PCO2 and CO2 apneic threshold) and by DeltaRR [response of respiratory rate (RR) to PSV]. We also wishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
2
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 27 publications
3
78
2
4
Order By: Relevance
“…When delivering high VT values through a ventilator, neuromechanical inhibition may occur (33,36). Although approximately the same VT was used under all three conditions, it may not have necessarily caused a comparable degree of neuromechanical inhibition at the three FI O 2 levels (8).…”
Section: Discussionmentioning
confidence: 99%
“…When delivering high VT values through a ventilator, neuromechanical inhibition may occur (33,36). Although approximately the same VT was used under all three conditions, it may not have necessarily caused a comparable degree of neuromechanical inhibition at the three FI O 2 levels (8).…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used analogy is the regulation of room temperature, whereby temperature will be prone to oscillation in a situation where there is a particularly sensitive thermostat and an overly powerful heater (i.e., high loop gain) (52). Techniques have been developed to measure loop gain of the respiratory system, such as the proportional assist ventilation (PAV) technique (53,54). Studies using PAV have demonstrated that patients with OSA do in fact have an elevated loop gain and suggest that ventilatory instability is an important mechanism contributing to sleep-disordered breathing (55,56).…”
Section: Ventilatory Control Stabilitymentioning
confidence: 99%
“…1 During sleep in PSV mode, inspiratory efforts are constant but tidal volume (V T ) oscillates, intermittently decreasing the P aCO 2 level below the apneic threshold, which is not very different from the P aCO 2 value in eupnea. 2 The apneic P aCO 2 threshold is physiologically lower during stage 1 sleep than during wakefulness.…”
Section: Introductionmentioning
confidence: 99%